SERUM ALBUMIN IN POORLY DIFFERENTIATED, ORAL SQUAMOUS CELLCARCINOMA: A POSSIBLE DIAGNOSTIC MARKER OF SIGNIFICANCE - Singh, Abhishek; M., Anitha; Yadav, M. M. (Archives of Oral Research, 2011)
Objectives: Serum albumin is considered to be the most potent and abundant extra-cellular anti-oxidant thatmight have a protective role in the ongoing process of transition of the various oral pre-cancerous lesions andconditions into frank malignant degenerations. The aim of this study was to check the reliability of serum albuminas one of the diagnostic anti-oxidant parameter. Materials and methods: The study consisted of seraanalysis of albumin in the age and sex matched normal healthy adults and patients with histologically proven,poorly differentiated oral squamous cell carcinoma. The results were analyzed using Student’s t-test andwere averaged as mean ± standard deviation. In above test, p-values less than 0.05 were taken to be statisticallysignificant. The normality of data was checked before the statistical analysis was performed. Results:The study revealed variations in sera levels of albumin to be statistically significant with the mean level ofsera albumin to be 4.956 ± 1.0579 in controls as against 3.6933 ± 1.2177 in patients with histologically proven,poorly differentiated, oral squamous cell carcinoma. Conclusions: The results of the study emphasize theneed for more studies with larger sample sizes to be conducted before a conclusive role could be drawn infavor of sera levels of albumin as diagnostic markers of significance in oral squamous cell carcinoma.